Maxillary transverse dimensions in subjects with and without impacted canines: a comparative cone-beam computed tomography study (2018)
Introduction: The objective of this study was to compare the maxillary transverse dimensions between subjects with impacted maxillary canines and subjects without canine impactions, with similar vertical and sagittal fea-tures. Methods: In this retrospective study, 86 cone-beam computed tomography images of subjects with impacted maxillary canines (45 unilateral, 41 bilateral) and 67 images of subjects without dental impactions(control group) matched by similar vertical (NSAr, SArGo, ArGoMe) and sagittal (ANB, SNA, APDI) skeletal characteristics, were analyzed. The maxillary width was measured at 4 levels: first molar basal width, first molar alveolar width, first premolar basal width, and first premolar alveolar width. Group comparisons were performed with analysis of variance and post-hoc Scheff e tests. The influence of group features on the transverse dimensions was evaluated by multiple linear regression analysis. Results: Groups with unilateral and bilateral impacted maxillary canines showed significantly smaller first molar basal widths, first molar alveolar widths, and first premolar alveolar widths compared with the control group (P50.030, P\0.001, andP\0.001, respectively). First premolar basal widths were not significantly different among the groups. Conclusions: Subjects with unilateral or bilateral impacted maxillary canines have smaller maxillary transverse dimensions than subjects without impaction. Orthodontists should consider the relationship of maxillary width and canine impaction during diagnosis and treatment planning